Summary of Determinants and impact of sustainable land and watershed management investments - Schmidt, Emily; Chinowsky, Paul; Robinson, Sherman; Strzepek, Kenneth M. (International Food Policy Research Institute, 2014)
Ongoing debate over water resource management and land degradation suggests a need for efficient sustainable land management mechanisms to improve agricultural output in the Blue Nile basin in Ethiopia. Numerous econometric and hydrological models have been developed to assess the effects of sustainable land and watershed management (SLWM) investments. However, these models fail to address the trade-offs faced by rural farmers in maintaining such structures. This study combines household survey data that evaluates the economic determinants of program sustainability with a detailed hydrological model that explores location specific effects of SLWM structures. Simulations suggest that more comprehensive investments (such as SLWM with increased fertilizer application) may reap more economically significant increases in household income. Cost benefit analysis suggests that a packaged investment approach is needed in order to outweigh the opportunity costs (foregone labor, particularly) of investing in SLWM infrastructure at farm level.